Factors influencing online impulse buying behavior during Covid-19 pandemic - Adnan, Nur Farahanim; Osman, Syuhaily (Human Resource Management Academic Research Society, 2022)
The main purpose of this study was to determine the influence of product availability, time availability, money availability on online impulse buying behavior during COVID-19 pandemic among consumers in Malaysia. There was a total of 300 respondents participated in this study. The data were collected through a Google Form that was distributed through social media platforms. The findings of Pearson correlation analysis demonstrated product availability (r = 0.530; p = 0.000), money availability (r = 0.636; p = 0.000) and money availability (r = 0.637; p = 0.000) had significant relationship with online impulse buying behavior. Meanwhile, the multiple linear regression analysis showed money availability (? = 0.373; p = 0.000) was the most significant variable that influence consumers online impulse buying behavior during COVID-19 pandemic. The findings of this study would be beneficial for consumers in identifying the factors that will lead them to conduct an online impulse buying behavior. Besides that, e-commerce business can plan for new business strategies that focus on money availability as the result of this study showed that money availability will trigger online impulse buying behavior during COVID-19 pandemic.